Gastro-Protective and Anti-Oxidant Potential of Althaea officinalis and Solanum nigrum on Pyloric Ligation/Indomethacin-Induced Ulceration in Rats - Sameh S. Zaghlool; Ali A. Abo-Seif; Mohamed A. Rabeh; Usama Ramadan Abdelmohsen; Basim A. S. Messiha (MDPI AG, 2019)
Recently, an alternative disease treatment approach is the research of medicaments from traditional medicine. Plants with anti-oxidant capabilities are used as herbal treatments for ulcer diseases. Medicinal/herbal extracts containing phytoconstituents have significant anti-ulcer activities in in vivo experiments on animal models, compared to reference drugs. The current study aims to inspect gastro-protective as well as in vitro and in vivo anti-oxidant potential of Althaea officinalis and Solanum nigrum extracts on pyloric-ligation/indomethacin-induced gastric-ulceration in rats. Rats were divided into six groups: normal control, gastric ulcer control, two standard pretreatment groups receiving omeprazole and misoprostol, and two test pretreatment groups receiving Althaea officinalis and Solanum nigrum. Pretreatments were administrated orally for 14 days. On the 15th day, animals, excluding the normal control group, were exposed to pyloric-ligation followed by indomethacin injection. After four hours, the rat’s stomachs were removed and gastric juice and blood samples were collected. Pyloric-ligation/indomethacin administration caused considerable elevation in ulcer number, ulcer index, acid and pepsin productivity, aggressive factors, and gastric mucosal lipid-peroxide contents. Moreover, reduction in titratable acidity, gastric mucosal nitric-oxide, anti-oxidant contents, and protective factors accompanied gastric-ulceration. Additionally, elevation in pro-inflammatory cytokines content and reduction in cystathionine-β-synthase and heme-oxygenase-1 expression was witnessed. Omeprazole, misoprostol, Althaea officinalis, and Solanum nigrum pretreatments fixed blood and tissue biomarkers, thereby protecting them from pyloric-ligation/indomethacin-induced gastric-ulceration in rats, which is hopeful for clinical examinations.